Nitrogen top-dressing fertilization of maize cultivated in single and twin-row systems1 - Brame, Lucas José [UNESP]; Coelho, Anderson Prates [UNESP]; Leal, Fábio Tiraboschi [UNESP]; Salvador, Almir [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP]; Lemos, Leandro Borges [UNESP] (Universidade Federal de Viçosa, 2021)
The aim of this study was to evaluate the effects of cropping systems (single and twin-rows) and N fertilizer rates in the second top-dressing on the agronomic performance and relative economic returns of maize. The experiment was conducted in a randomized block design, with subplots and three repetitions. The plots were composed of two cropping systems: single and twin-rows. The subplots consisted of six rates of N fertilizer, applied in the second top-dressing fertilization in the V8 phenological stage (eight fully developed leaves) of maize: 0, 14, 28, 56, and 70 kg ha-1 of N. The first application of N top-dressing fertilization (rate of 140 kg ha-1 N) was during the V4 phenological stage (four fully developed leaves) in all treatments. The cropping system of twin-rows provides a higher grain yield and relative economic return of maize. The agronomic efficiency of the twin-row cropping system decreases with increasing N rates, but remains higher than that obtained in the single-row system, independent of the N fertilizer top-dressing rate.. The application of the second N top-dressing fertilization in the V8 phenological stage increases linearly with the grain yield and relative economic return of maize, independent of the cropping system.
Keywords: Zea mays L.; nitrogen rates; twin-rows; agronomic efficiency.